RANCANG BANGUN FUNCTION GENERATOR BERBASIS ARDUINO DENGAN FUNGSI PERIODIK SEBAGAI MASUKAN - Muhammad Setyo Hadi Juwono; Ponco Siwindarto; Zainul Abidin (Jurnal Mahasiswa TEUB, 2023)
Function generator is one of the most important and versatile electronic test equipment. Some of its users and uses are research and development, educational institutions, electrical and electronic equipment repair businesses, stimulus/response testing, frequency response characterization, incircuit signal injection, and hobbyist electronics. The waveforms that can be generated by the function generator include Sine waves, Square waves, Sawtooth waves and Triangle waves. The traditional analog function generators are gradually being replaced by digital function generators. However, the existence of function generators in the market has many problems such as high cost, large size, use of complicated methods, troublesome settings, unfriendly interface and so on. Referring to the above problems, an Arduino-based function generator was designed with adjustable input amplitude and frequency. This study aims to offer a function generator option with easy settings for users from electronics hobbyists in designing and testing electronic devices that are currently under development. The use of Arduino in this tool which is the most commonly used Development Board on the market and has a large user community is intended so that users can more easily access this tool and also aims to make it easier to manage the use of this tool. Based on the test results, the Arduino Due's DAC output has an average error of 0.647% with an accuracy of 99.353%. Testing the signal conditioning circuit has an average error of 0.218% with an accuracy of 99.782%. Testing the entire system has an average Vpp error of 0.340% with an accuracy of 99.660% and an average frequency error of 0.054% with an accuracy of 99.946%. Keywords: Function Generator, DAC, Op-Amp